Self-Organized Ad Hoc Mobile (SOAM) Underwater Sensor Networks. - Hyder, Waheeduddin; Kumar, Jitander; Luque-Nieto, Miguel Ángel; Laghari, Asif Ali; Otero-Roth, Pablo (IEEE, 2022)
The need of underwater wireless sensor networks (UWSNs) having mobile sensor nodes has been there for a long time in form of underwater warfare or explorations by autonomous underwater vehicles (AUVs) or remote unmanned vehicles (ROVs). There are very few protocols for ad hoc mobile UWSNs (AMUWSNs). Designing a protocol for AMUWSN is quite challenging because of continuous random movement of the sensor nodes. In addition to random movement, the challenges to design a routing protocol for AMUWSN are more demanding than terrestrial ad hoc networks due to acoustic communications, which has large propagation delay in water. In this article, we present a self-organized ad hoc mobile (SOAM) routing protocol for AMUWSN. The sensor nodes may need to communicate with each other to the gateway (GW). The protocol, which we also refer to as SOAM, is a reactive, self-configuring, and self-organizing cluster-based routing protocol that uses received signal strength (RSS) for distance estimation. A beacon (BCN) packet will be sent by the GW, which will traverse through all the cluster heads (CHs) to form forwarding paths between the GW and the CHs. The ordinary sensor nodes (OSNs) will select the CHs every time they intend to forward a packet based on the BCN and they will receive from CHs. The formation of the forwarding path between the GW and the CHs and the selection CHs by OSN is explained in Section IV.
Política de acceso abierto tomada de: https://beta.sherpa.ac.uk/id/publication/3570
Keywords: Ondas sonoras; Protocolos de comunicaciones; Sistemas de comunicaciones inalámbricos; Ingeniería - Aparatos e instrumentos; Routing protocols; Routing; Ad hoc; Location free; Proactive; Self-configured; Self-organized; Underwater wireless sensor network (UWSN)